Endoscopic Submucosal Single- or Multi-tunnel Dissection for Near-Circumferential and Circumferential Superficial Esophageal Neoplastic Lesions. (12th March 2019) - Zhu, Lin-Lin; Wu, Jun-Chao; Wang, Yi-Ping; He, Du; Zhang, Wen-Yan; Gan, Tao; Yang, Jin-Lin
Abstract : This study reports the outcomes of endoscopic submucosal single-tunnel dissection or endoscopic submucosal multi-tunnel dissection for the treatment of esophageal neoplastic lesions of at least three-quarters of the esophageal circumference, including circumferential superficial esophageal neoplastic lesions. From July 2014 to February 2018, a total of 124 lesions underwent endoscopic submucosal tunnel dissection at our hospital. One to four submucosal tunnels were created in the oral to anal direction. Of the 124 lesions, there were 83 noncomplete circumferential lesions and 41 circumferential lesions. Endoscopic submucosal single-tunnel dissection was performed in 54 patients, two-tunnel dissection in 43 patients, three-tunnel dissection in 19 patients, and four-tunnel dissection in 8 patients. The mean dissection speed was22.8 ± 12.7   mm 2 / min . En bloc dissection was achieved in all lesions, and the R0 resection rate was 70.2 percent. No matter how large the lesion area was, there were no significant differences in the dissection speed and the R0 resection rate when lesions were at least three-quarters of the esophageal circumference. Esophageal stricture was observed in 54 patients and was relieved by placement of a retrievable metal stent or by endoscopic water balloon dilation. No recurrence was noted after19.1 ± 12.4 months of follow-up. Our large sample size study showed that endoscopic submucosal tunnel dissection showed effectiveness and safety for the treatment of large superficial esophageal neoplastic lesions at least three-quarters of the esophageal circumference, including circumferential superficial esophageal neoplastic lesions.